Цифровая грамотность как средство от инфодемии Covid-19 в Индонезии (Digital Literacy as an Antidote to Covid-19 Infodemic in Indonesi) - Cut Fitri Indah Sari Hoesin; Natalia V. Poplavskaya; Barek Hossain (Jurnal Cita Hukum, 2022)
Since the beginning of the pandemic, incorrect information or fake news related to the Covid-19 spread out uncontrollably and caused panic and unrest in the community. This is in line with the report from Ministry of Communication and Information of Republic Indonesia that shown as February 2022, there is 2121 fake news related to Covid-19 or infodemic circulated in social media in Indonesia. For this reason, the need for the role of digital literacy in preventing and anticipating infodemic discussed in this paper. Using qualitative research approach with library research methods, it was found that the need of digital literacy to raise awareness of selecting and checking the sources of information, training critical thinking to every information, the importance of developing skills to identify incorrect information, and correcting infodemic in the society.